Techno-economic viability and environmental sustainability of a grid-connected solar PV system for small and medium scale businesses in Cape Coast–Ghana using RETScreen expert - Kwame Anane-Fenin; Nana Yaa Serwaah Sarpong; Theophilus Adu Frimpong; Mukuna Patrick Mubiayi; Richmond Kuleape; Damenortey Richard Akwada; Wisdom Eyram Kwame Agbesi; Juliana Sally Renner; Charles Emmanuel Oppon; Lawrence Atepor; Felix Menu (Cogent Engineering, 2025)
Ghana is home to some of West Africa’s largest markets which have high energy consumption levels. This presents significant opportunities for solar energy investments. The study assesses the technical, economic and environmental viability of implementing three solar photovoltaic systems for three categories of small and medium-sized enterprises based on their energy demand. The results showed a promising energy yield of 1.42 kWh/yr per watt and a capacity factor of 16.3%. However, the economic analysis presented significant challenges such as a payback period ranging from 17.8 to 20.3 years, negative Net Present Value and levelized cost of energy higher than the base case grid electricity price. The environmental analysis demonstrated substantial potential for greenhouse gas emission reduction, with all systems achieving a 93% decrease compared to the local grid. A policy impact analysis was conducted to highlight industry-approved and research-based policies that meet global best practices.